2014
DOI: 10.1016/j.jhep.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor NRF2 protects mice against dietary iron-induced liver injury by preventing hepatocytic cell death

Abstract: Background & Aims:The l i v e r , being the major site of i r o n storage, is particularly exposed to the toxic effects of iron. Tran-scription factor NRF2 is critical for protecting the l i v e r a g a i n s t disease by activating the transcription of genes encoding detoxification/antioxidant enzymes. We aimed to determine if the NRF2 pathway plays a significant role in the protection against hepatic iron overload. Methods: Wild type and Nrf2 _ /_ mouse primary hepatocytes Wereincubated with ferric ammonium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…HO-1 and NQO1 are regarded as antioxidants that act downstream of Nrf2 [34]. In previous studies, it had been demonstrated that NQO1 expression was mediated by Nrf2 [36,37], and more importantly, HO-1 expression upregulation is always considered to be the evidence for the activation of Nrf2 signaling pathway [38]. NQO1 facilitates scavenging of ROS generated by mitochondria [39e42], and HO-1 exerts multiple regulatory functions during oxidative stress [43e47].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 and NQO1 are regarded as antioxidants that act downstream of Nrf2 [34]. In previous studies, it had been demonstrated that NQO1 expression was mediated by Nrf2 [36,37], and more importantly, HO-1 expression upregulation is always considered to be the evidence for the activation of Nrf2 signaling pathway [38]. NQO1 facilitates scavenging of ROS generated by mitochondria [39e42], and HO-1 exerts multiple regulatory functions during oxidative stress [43e47].…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented DNA was detected through TdT-mediated dUTP nick-end labeling (TUNEL) staining as described by Silva-Gomes et al [15]. For the detection of F4/80, samples were blocked with 5% bovine serum albumin and 0.05% Tween 20 in phosphate buffer and incubated with rat anti-F4/80 (Serotec, Oxford, UK), followed by goat anti-rat IgG AlexaFluor 647 (Life Technologies, Carlsblad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that livers of Nrf2 -/- mice are more susceptible to oxidative/electrophilic stress than those of wild-type mice [12], [13], and NRF2 is increasingly regarded as an important modifier of chronic liver diseases [14]. Recently, we have reported that iron activates NRF2 in mouse hepatocytes and that NRF2 is important for the viability of hepatocytes during exposure to acute dietary iron overload [15]. To test the hypothesis that NRF2-mediated resistance to oxidative/electrophilic stress may be a modifier of disease progression in HFE-HH, we aimed to evaluate if the genetic suppression of Nrf2 would predispose the Hfe -/- mouse to spontaneous liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in iron regulatory genes modulate iron loading in humans with thalassemia syndromes [100, 163168], while mutations in oxidant protective pathways modulate the clinical expression of hemoglobinopathies [169173] and have been associated with other disorders, including propensity to malignancy [174177]. The FOXO3 family of transcription factors plays a major role in the regulation of oxidative stress, is essential for red cell survival and its absence results in early red cell maturation arrest that can be partly rescued by antioxidant treatment [95, 178, 179].…”
Section: Iron Toxicitymentioning
confidence: 99%